PEMBELAJARAN KOLABORATIF BERSAMA PRAKTISI BIDANG PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DALAM MENGIMPLEMENTASIKAN PERMENLHK NO. 6 TAHUN 2021 - Maziya, Fina Binazir (Universitas Islam Indonesia, 2024)
Collaborative learning with practitioners is an effort to enhance the learning atmosphere in the classroom, helping students better understand and explore materials that predominantly apply regulations in Indonesia. The practitioners involved are alumni of the Environmental Engineering Study Program, who have an emotional connection with the students, fostering a sense of familiarity and comfortable communication. These practitioners provide insights and reinforcement of materials related to hazardous and toxic waste (B3) management systems in the industrial sector, particularly in the areas of their expertise. Students are assigned case studies to prepare environmental documents related to B3 waste management in the industrial field. They engage in mentoring sessions with practitioners to facilitate a